Koping Lanjut Usia yang Diserahkan Keluarga ke Panti Wredha Dharma Bhakti Surakarta - Ari, Ryan Avri, Arif Widodo, A.Kep., M.Kes, Wachidah Yuniartika, S.Kep., Ns (2013)
Elderly live in Dharma Bhakti Retirement Home Surakarta use their adaptive coping, this corresponds with activity theory stating that the older a person is, the more they maintain their social, physical and emotional relationships. While the main support system of elderly in family member i.e. spouse, children, and grandchildren. Therefore the researcher is attracted to do a research about coping of elderly handed by family to Dharma Bhakti Retiremnt Home Surakarta. The general purpose of this research is to find out the idea of coping of elderly handed by family to Retirement Home. The method used is qualitative research. The research approached used is phenomenology approach. Data collection method used is in depth interview using semi structured interview form. The researcher also used focus group discussion method. There are 6 informants as samples in this research. Data analisis steps taken is data analisis on interactive model proposed by Miles and Huberman, which are Data Reduction, Data Disply, and Conclusion Drawing. Based on analisis attachment on categorizing of 10 questions given to each informan, it is deduced thet elderly in retirement home utilize adaptive coping and maladaptive coping. Adaptive coping is shown by getting closer to god, conduct something heart pleasing, mingle selectively, reciprocally communicate and recognize, conduct good deed. Maladaptive coping is sown by showing negative deed. The research resulted thet elderly handed by family to retirement home utilize adaptive and maladaptive coping as a response to a threat. Retiremnt Home is expected to develop social support system towards fellow elderly residents by organizing a discussion activity among elderly or group activity therapy thet boosts communication and intimacy among elderly.